AMBIGUITAS, KONFLIK PERAN, INTEGRITAS SERTA INDEPENDENSI SEBAGAI DETERMINAN KUALITAS AUDIT INTERNAL (Studi Empiris Pada Kantor Akuntan Publik Kota Semarang) - Anggiat Sonny Hutapea, 12.05.52.0221; Alfasadun, Alfasadun (Students' Journal of Accounting and Banking, 2016)
The study aims to examine and analyze the ambiguity, role conflict, integrity, and independence as a determinant of the quality of internal audit. The study consists of three independent variables that ambiguity, role conflict, and integrity. The dependent variable in this study is the Independence and Quality of Internal Audit.  This study used survey method with questionnaires in collecting data. Respondents were sampled in this study is the Auditor number of 40 respondents in the public accounting firm in the city of Semarang.   The results showed an effect on Independence Ambiguity, Role Conflict does not affect the Independence and Integrity effect on Independence. Ambiguity does not affect the quality of the internal audit, role conflict does not affect the quality of the internal audit, internal audit Integrity affect the quality and independence of the effect on the quality of internal audit. Independence does not successfully mediate between ambiguity effect on the quality of internal audit, the independence of not successfully mediate the association between the conflicting roles of the quality of internal audit, and the independence does not successfully mediate the relationship between the integrity of the internal audit quality.  Keywords: Ambiguity, Role Conflict, Integrity, Independence, Internal Audi Quality